2016
DOI: 10.1016/j.isprsjprs.2016.10.009
|View full text |Cite
|
Sign up to set email alerts
|

Characterizing major agricultural land change trends in the Western Corn Belt

Abstract: a b s t r a c tIn this study we developed annual corn/soybean maps for the Western Corn Belt within the United States using multi-temporal MODIS NDVI products from 2001 to 2015 to support long-term cropland change analysis. Based on the availability of training data (cropland data layer from the USDA-NASS), we designed a cross-validation scheme for 2006-2015 MODIS data to examine the spatial generalization capability of a neural network classifier. Training data points were derived from a three-state subregion… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
8
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 23 publications
(8 citation statements)
references
References 37 publications
0
8
0
Order By: Relevance
“…To further verify the accuracy of crop identification results, the correct identification percentage of different crops and Kappa coefficient (Table 6) were calculated using the verification points in 2014 and 2015 (Figure 1). The correct identification rates of different crops were all greater than 70% and the Kappa value of consistency test was 0.62, which indicated that the classifier performance was acceptable [15]. We also selected a specific micro-scale area (19.36 ha) of Hetao Irrigation District to analyze the classification results; the detailed description of this area can be referred to Ren et al [4].…”
Section: Comparison Of Identification Results Of Nine Classifiersmentioning
confidence: 99%
“…To further verify the accuracy of crop identification results, the correct identification percentage of different crops and Kappa coefficient (Table 6) were calculated using the verification points in 2014 and 2015 (Figure 1). The correct identification rates of different crops were all greater than 70% and the Kappa value of consistency test was 0.62, which indicated that the classifier performance was acceptable [15]. We also selected a specific micro-scale area (19.36 ha) of Hetao Irrigation District to analyze the classification results; the detailed description of this area can be referred to Ren et al [4].…”
Section: Comparison Of Identification Results Of Nine Classifiersmentioning
confidence: 99%
“…The land use differed by year in the study region [30,31], and a cropland mask was prepared to identify spatial pixels where the land use was classified as cropland throughout the period from 2001-2016 (Figure 1a). A crop-specific mask for corn and soybean would have been preferable as its use could improve the accuracy of crop yield forecast.…”
Section: Satellite Data Productsmentioning
confidence: 99%
“…Nationwide (Lark et al., ; Wright et al., ) and regional analyses (Lu et al., ; Shao, Taff, Ren, & Campbell, ; Wright & Wimberly, ) identify North and South Dakota as having some of the greatest land use changes in the United States over the last several decades. These types of analyses are improving due to increasing availability of datasets, tools, and new methodology for geospatial analyses.…”
Section: How Are Cropping Patterns Changing?mentioning
confidence: 99%